Clinical impacts of the Sudanese anatomical variations in a relation of the recurrent laryngeal nerve to the inferior thyroid artery - Elghazali Elhasan, Mohamed; Mohialddin Doush, Wael (International Journal of Medicine, 2020)
Background: Until recently, the knowledge of the anatomical variations in the relationship between the recurrent laryngeal nerve (RLN) and the inferior thyroid artery (ITA) combined with visual intraoperative RLN identification are essential for the protection of these life-important structures during surgical exposure and the mobilization of thyroid and parathyroid glands. This leads to the proper treatment of patients and improvement of the surgical techniques.Aim: To describe anatomical variations in the relationship of the recurrent laryngeal nerve to the inferior thyroid artery in the Sudanese population.Patients and methods: Following ethical committee approval, an observational descriptive prospective cross-sectional study in the period between March 2019 and February 2020, for anatomical variations in the relation of the recurrent laryngeal nerve to the inferior thyroid artery in seventy-two cervical sides of thirty-six well-dissected embalmed Sudanese cadavers. The RLN was investigated in three positions: posterior to the ITA main trunk, anterior to the ITA main trunk and between the ITA branches. Then, the results were analyzed according to the gender, age and dissection side.Results: We found that the anatomical variations were more frequent in males (97.2%) than females (2.8%). The age of these variations ranged between 31â€“45 years which represents (61.1%). On the right side of the neck, the commonest position of the RLN is posterior to the ITA (63.9%) followed by in decreasing order of frequency, the RLNs run between the ITA branches (30.6%) and anterior to the ITA (5.6%). On the left side of the neck, the commonest position of the RLN is posterior to the ITA (69.4%). It passed between the ITA branches in (30.6%) of specimens. There was no anterior location of the RLN to the ITA. Variations in a relationship of the RLN to the ITA on one side is significantly different from the opposite side.Conclusions: Although the risk of potential damage to the RLN during surgical neck procedures involving the thyroid gland and parathyroid glands is well recognized, pre-operative detailed surgeonâ€™s knowledge for these frequent anatomical variations and the usage of the ITA as an anatomical landmark for intraoperative RLN recognition is important. This will lead to a reduction of iatrogenic RLN injury prevalence. Future studies are recommended to compare the findings on this cadaveric study with a larger sample size in the long-term period.Â Â